Studi Tentang Upaya Peningkatan Jumlah dan Kualifikasi Teknisi Pesawat Udara Di Indonesia - Nurhadi Abu Zaka (Institut Teknologi Dirgantara Adisutjipto, 2016)
The development of the aviation industry in Indonesia increased significantly the last few years, so it is necessary adequate Aircraft Technician/Engineer (TPU), both the number and qualifications. The problem is, the amount of TPU in Indonesia is very limited and the majority academic level only senior high school, it making less competitive. The purpose of study to find out efforts to increase the number and qualifications of TPU by PT GMF Aero Asia Garuda Group (GMFAA) is cooperating with six universities in Indonesia to produce TPU with D-III level. Studies done by observation, interview and direct involvement at the Basic Aircraft Maintenance (BAM) for instructor, organized by GMFAA for 1,920 hours. The data were analyzed descriptively to obtain qualitative research. The study shows that in the first batch (2015-2016) has trained 16 lecturers of 6 universities to conduct AMTO class at each campus. In the first year (2015) has opened AMTO classes at six campuses with 226 students and 216 in the second year (2016). From the 4th year (2018) will certainly be produced aircraft technician/engineer with D-III qualifiers at least 200 people, so it's very helpful to accelerate the fulfillment of TPU in Indonesia Keywords— Aircraft Technician/Engineer, maintenance, AMTO